Dynamics of Intermittent Viremia during Highly Active Antiretroviral Therapy in Patients Who Initiate Therapy during Chronic versus Acute and Early Human Immunodeficiency Virus Type 1 Infection - Di Mascio, Michele (American Society for Microbiology, 2004)
The meaning of viral blips in human immunodeficiency virus type 1 (HIV-1)-infected patients treated with seemingly effective highly active antiretroviral therapy (HAART) is still controversial and under investigation. Blips might represent low-level ongoing viral replication in the presence of drug or simply release of virions from the latent reservoir. Patients treated early during HIV-1 infection are more likely to have a lower total body viral burden, a homogenous viral population, and preserved HIV-1-specific immune responses. Consequently, viral blips may be less frequent in them than in patients treated during chronic infection. To test this hypothesis, we compared the occurrence of viral blips in 76 acutely infected patients (primary HIV infection [PHI] group) who started therapy within 6 months of the onset of symptoms with that in 47 patients who started HAART therapy during chronic infection (chronic HIV infection [CHI] group). Viral blip frequency was approximately twofold higher in CHI patients (0.122 ± 0.12/viral load [VL] sample, mean ± standard deviation) than in PHI patients (0.066 ± 0.09/VL sample). However, in both groups, viral blip frequency did not increase with longer periods of observation. Also, no difference in viral blip frequency was observed between treatment subgroups, and the occurrence of a blip was not associated with a recent change in CD4(+) T-cell count. Finally, in PHI patients the VL set point was a significant predictor of blip frequency during treatment.